A One‐Pot Oxidation/Enantioselective Oxa‐Michael Cascade. Issue 14 (24th February 2014) - Willemsen, Jorgen S.; Megens, Rik P.; Roelfes, Gerard; van Hest, Jan C. M.; Rutjes, Floris P. J. T.
Abstract: A laccase/(2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxy (TEMPO) mediated oxidation was combined with an aqueous, enantioselective copper‐catalyzed Michael addition reaction of water in one pot. The copper catalyst was also immobilized onto DNA to induce enantioselectivity in the reaction. Low conversions were observed when the reactions were performed simultaneously, caused by an undesired reaction of an oxidised TEMPO intermediate. We increased the conversions by using a stepwise approach. Thus, after completion of the oxidation, the first reaction was stopped by inhibiting the enzyme with HCO2 K and reducing the reactive TEMPO intermediate. Next, the Michael addition reaction was started by adding the Cu catalyst. By applying this strategy, an efficient two‐step one‐pot sequence, proceeding with 20 % ee, was realized. The yield and ee of the second reaction were not affected by the oxidation reaction. Abstract : A one‐pot reaction was developed containing a laccase/(2, 2, 6, 6‐tetramethylpiperidin‐1‐yl)oxy‐mediated oxidation followed by a DNA‐based, copper‐catalysed oxa‐Michael addition reaction. The enantioselective oxa‐Michael addition reaction only occurred if the sequence was performed stepwise and the first reaction was inhibited with HCO2 K.